Examination of Physical Changes and Counselling Premenopausal Women In Cilayung Village, Jatinangor District - Sefita Aryuti Nirmala; Nadia Khansa Fauziyyah; Sharon Gondodiputro (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2022)
Perimenopause is the period always starts with an irregular menstrual cycle to the last menstrual period. The World Health Organization estimates that by 2030, 1.2 billion women worldwide will reach menopause. In Indonesia, in 2025, there will be around 60 million menopausal women. Cilayung Village is one of the villages in the Jatinangor district which is 4 KM from district center and the campus area. Although not far from the district center, Cilayung Village does not care about the changes that have occurred. Information given by village midwives on perimenopausal women showed that, in a month there could be 2 to 5 women found to be in their perimenopausal period. Also there were no health data about perimenopausal women. The methods of this community service were carried out in stages: 1) analysis of the situation of perimenopausal women, 2) problem identification, 3) determining work goals, 4) problem solving planning, 5) close social interaction, 6) implementation of activities, and 7) evaluation. Village midwives and cadres assited with the activities mentioned above. A total of 106 perimenopausal women participated, and they were examined to physical changes, and there were collected as data. The data collected showed vasomotor instability or hot flashes (at least 54.70%), not experiencing vaginal dryness (90.60%), low osteoporosis or OSTA status (45.30%), and cholesterol status (the most common was 78.30%). Health promotion and counselling were given, and a presentation followed by a Q and A session on perimenopausal women was also organized.